Tombamento e a justa composição para o patrimônio cultural - Spaolonzi, Maria Gabriella Pavlopoulos (2018)
The aim of this study is the balanced protection of the rights reached by state intervention in the ownership of urban real estate in the form of tipping. To achieve this aim, in the first part, we discuss the concepts elevated to the constitutional guarantee. More precisely, on the elements that make up the concept of cultural heritage as well as the right to property. From the valorization of the right to culture, which is also constitutionalised, a new meaning of the social function of property is focused in order to conclude that property has lost its absolute character over the years. This research then visited the various forms of state intervention in private property to devote greater attention to tipping - the most important instrument of our legal system for the protection of cultural heritage. A special chapter was dedicated to the indemnification aspect of tipping to conclude that the aforementioned form of state intervention, often responsible for serious damage to the holder of the domain, accommodates itself in social resilience. From this conclusion, the study dealt with the right of indemnification of the individual and some forms of its concretization. The second part of the study devoted attention to the Vila Operária Maria Zéliae, located in the neighborhood of Belém, in São Paulo. This village was established more than one hundred years ago. This Villa suffers from the effects of the tipping since the 1980s. This state intervention has in many cases configured the total misconfiguration of the property with total damage to the cultural patrimony. For what possible solutions can concrete case await? The conclusion of the study highlights the need to apply instruments aimed at provoking the responsibility of the parties affected by the tipping. As for the particular, the need for it to be called to respond for the effective maintenance of the good even in the form of its provocation in the hypotheses in which it does not have the financial resources for such purpose. In relation to the Public Power, to respond for the damages caused not only to the particular but to the cultural patrimony in the situations in which it remains inert even when the hype and lack of knowledge of the owner of the domain was a known fact even before the concretization of his intervention in his property .